Surgical Management of Cervico-Vaginal Prolapse Concurrent with Pyometra in a Six-and-a-Half-Year-Old Labrador Crossbred Bitch - Baishya, Mridu Pawan; Khargharia, Sanjib; Baruah, Himangshu; Khuman, L. Sanathoi; Baruah, Aditya; Mahanta, Dwipjyoti; Deka, Suraksha Subedi; Patowary, Prerona; Kalita, Manoj Kumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
A-six-and-half-year-old female Labrador crossbred dog was presented to the Veterinary Clinical Complex, Lakhimpur College of Veterinary Science, Assam Agricultural University, Joyhing with a two-day make days history of prolapsed mass visible through the vaginal route. The client revealed that, the animal exhibited straining followed by the appearance of a reddish, elongated mass protruding from the vaginal opening accompanied by sticky or milky discharge during the later stages of straining. Additionally, the dog had reduced appetite, frequent vomiting, and intermittent straining episodes. Clinical examination confirmed cervico-vaginal prolapse, with the protruded mass appearing edematous and hyperemic, though the urinary bladder was not involved. Further assessment included hemato-biochemical evaluation, along with ultrasonographic examinations of the abdominal and pelvic cavities. Imaging findings revealed anechoic spaces in the pelvic region, suggestive of pyometra. An exploratory laparotomy was performed through a caudal mid-ventral incision. During surgery, the prolapsed mass was repositioned into the pelvic cavity by gently pulling the uterine horn, following lubrication of the tissue with coconut oil to minimize trauma. Upon exploration, the uterus was confirmed to have open pyometra, necessitating a panhysterectomy (complete removal of the uterus and ovaries). The bitch recovered well post-operatively. Skin sutures were removed on the 14th day, and the surgical wound healed without complications. In this rare case of cervico-vaginal prolapse with pyometra, diagnostic imaging and hemato-biochemical analysis enabled accurate diagnosis. Prompt surgical intervention proved effective, preventing complications and ensuring a favorable prognosis.